2019
DOI: 10.1177/1545968319886485
|View full text |Cite
|
Sign up to set email alerts
|

Moving Stroke Rehabilitation Research Evidence into Clinical Practice: Consensus-Based Core Recommendations From the Stroke Recovery and Rehabilitation Roundtable

Abstract: Moving research evidence to practice can take years, if not decades, which denies stroke patients and families from receiving the best care. We present the results of an international consensus process prioritizing what research evidence to implement into stroke rehabilitation practice to have maximal impact. An international 10-member Knowledge Translation Working Group collaborated over a six-month period via videoconferences and a two-day face-to-face meeting. The process was informed from surveys received … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 24 publications
1
22
0
Order By: Relevance
“…Stroke Recovery and Rehabilitation Roundtables bring physiotherapists and other experts together to recommend research directions and produce guidance for the post-stroke healthcare system. Optimized delivery of stroke care systems and access to rehabilitation services are the future of healthcare for stroke [ 166 ].…”
Section: Trends In Stroke Researchmentioning
confidence: 99%
“…Stroke Recovery and Rehabilitation Roundtables bring physiotherapists and other experts together to recommend research directions and produce guidance for the post-stroke healthcare system. Optimized delivery of stroke care systems and access to rehabilitation services are the future of healthcare for stroke [ 166 ].…”
Section: Trends In Stroke Researchmentioning
confidence: 99%
“…Constraints such as limited time, personnel, or resources, affect the amount of therapy that can be delivered in inpatient and outpatient rehabilitation settings. For example, Lang et al [5] found that patients in an outpatient stroke unit practiced an average of only 41 active and purposeful movement repetitions of the upper limb per session, far below the number needed for motor skill acquisition and the recommended dose according to national and international stroke rehabilitation guidelines [6]. To address this problem, VR training platforms may be used as adjunctive therapy in which opportunities for extended practice may be made available for patients with supervision in groups or with specialized support personnel [7].…”
Section: Origin and State-of-the-artmentioning
confidence: 99%
“…For lower limb functions of balance and gait in patients with mostly post-acute stroke, de Rooij et al (18) found that virtual rehabilitation was more effective when added to conventional therapy and dose-matched for time in therapy, compared to conventional treatment alone. Thus, virtual rehabilitation as an adjunctive therapy has the benefit of increasing the amount of therapy delivered to the patient, which is linked to better outcomes, and has made its way into clinical practice guidelines for stroke care [6]. However, there is still a lack of evidence of the effectiveness of virtual reality applications for cognitive post-stroke rehabilitation and on participation and activities of daily living [17].…”
Section: Does Virtual Rehabilitation Deliver These Practice Environmementioning
confidence: 99%
“…Our findings, combined with evidence-based recommendations made in the aforementioned studies [41,48,49], will inform future enhancements to G-AP training and implementation strategies (see Table 7). This will be a focus of our ongoing research, the overall aim of which is to fully develop G-AP as a complex intervention (including training, supporting resources, implementation tools and strategies) ready for implementation and evaluation in a suitably designed large scale study.…”
Section: Implications For Research and Practicementioning
confidence: 65%